NICC - null (IEE Colloquium on How to Compete and Connect: Understanding the Engineering of Telecommunications Network Interconnection, 1997)
BACKGROUND: The paediatric intensive care unit exposes critically ill children to non-physiological environmental stimuli, such as noise, artificial light and thermal instability, which may interfere with physiological regulation and circadian organization. AIM: To examine how environmental conditions in the paediatric intensive care unit (PICU), including noise, lighting and ambient temperature, affect cardiovascular, respiratory and thermoregulatory physiology in paediatric patients admitted after extracorporeal cardiac surgery. STUDY DESIGN: This prospective cohort study used continuous environmental monitoring and repeated physiological measurements in a tertiary-level paediatric intensive care unit. Environmental variables were recorded at 30-s intervals and aggregated to 15-min resolution to align with routinely collected physiological data. Associations between environmental exposures and heart rate, blood pressure, respiratory rate, oxygen saturation and rectal temperature were evaluated using generalized additive mixed models (GAMMs) incorporating cyclic terms to account for circadian variation and patient-level random effects. RESULTS: Twenty-seven paediatric patients aged 0-14 years were analysed. Environmental factors showed consistent non-linear associations with cardiovascular and respiratory parameters. Heart rate and respiratory rate were the most sensitive variables, particularly in relation to visible light exposure, whereas blood pressure, oxygen saturation and rectal temperature showed comparatively attenuated responses. Despite critical illness, several physiological outcomes continued to exhibit significant 24-h temporal variation throughout the observation period. Age influenced baseline physiology but did not substantially modify the direction of environmental associations. Noise levels consistently exceeded recommended thresholds and lighting patterns lacked a structured day-night cycle. CONCLUSIONS: PICU environmental conditions were associated with changes in key physiological systems in paediatrics following extracorporeal cardiac surgery and may contribute to altered temporal physiological organization. RELEVANCE TO CLINICAL PRACTICE: Environmental optimization strategies-particularly structured light-dark cycles and noise reduction warrant further investigation as potential nursing-led interventions to support physiological regulation and circadian organization in paediatric critical care.